Collisions of sailing vessels with cetaceans worldwide: First insights into a seemingly growing problem - Ritter , Fabian (J. Cetacean Res. Manage., 2023)
Vessel-whale collisions are of growing concern worldwide, but information about collisions involving sailing vessels is especially scarce. This study represents the first global quantification of this kind. A total of 111 collisions and 57 near misses were identified, spanning from 1966 until 2010; 75% of cases was reported for the period from 2002–2010, suggesting an increasing trend. Reported collisions and near misses occurred on all oceans, often during ocean races and regattas, and were most frequent in the North Atlantic. Vessel type and speed as well as circumstances of the incident varied widely, but most often monohulls were involved, predominantly sailing at speeds between 5 and 10 knots. Most reports referred to ‘large whales’ as opposed to ‘small whales’ or ‘dolphins’. The species could be identified in 54 cases. Most recognised animals were humpback or sperm whales. Injuries to the whales varied strongly from ‘not visible’ to ‘dead after collision’, but mostly could not be determined. Sailing crew members were hurt in several cases, including collisions occurring at low speeds, and collisions often damaged vessels, including major impairment and seven cases of vessel loss. The findings presented here suggest that elevated vessel speed contributes to a higher risk of collisions. Conversely, the outcome of a collision (e.g. injury to whale or crew, damage to vessel) appears not to be a direct function of vessel speed. Several measures are discussed which potentially can contribute to mitigating the problem, including placing watchposts, an open dialogue with regatta organisers, changes in the design of regattas and ocean races and public outreach initiatives.